2019
DOI: 10.3390/ma12101652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium-Slag in the Performance of Slag Cement Mortar Based on Least-Squares Support Vector Machine Prediction

Abstract: There is a universally accepted view that environmental pollution should be controlled while improving cement mortar natural abilities. The purpose of this study is to develop a green cement mortar that has better compressive strength and anti-chloride ion permeability. Two industrial wastes, lithium-slag and slag, were added to cement mortar, and the role of lithium-slag was to activate slag. In addition, to save economic and time costs, this paper also used the least-squares support vector machine (LS-SVM) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It is a waste residue from lithium carbonate (Li 2 CO 3 ) production, and estimates suggest that about 10 tons of LS are generated for each ton of Li 2 CO 3 produced [25]. The chemical composition of LS mainly consists of SiO 2 , Al 2 O 3 and sodium oxide (Na 2 O) [26]. Fayalite slag (FS) is another industrial waste slag used in one-part AAMs [27,28].…”
Section: Industrial By-products and Waste Materialsmentioning
confidence: 99%
“…It is a waste residue from lithium carbonate (Li 2 CO 3 ) production, and estimates suggest that about 10 tons of LS are generated for each ton of Li 2 CO 3 produced [25]. The chemical composition of LS mainly consists of SiO 2 , Al 2 O 3 and sodium oxide (Na 2 O) [26]. Fayalite slag (FS) is another industrial waste slag used in one-part AAMs [27,28].…”
Section: Industrial By-products and Waste Materialsmentioning
confidence: 99%
“…Additionally, being a porous mineral material [ 70 ], LS stores free water within its pore structure, which increases the water retention in the concrete and reduces water evaporation. This, in turn, effectively minimizes drying shrinkage [ 13 ].…”
Section: Durability Of Cementitious Composites With Ls Incorporationmentioning
confidence: 99%
“…LS, which is rich in silicon, aluminum, and calcium oxides, has garnered interest as a substitute for ordinary Portland cement (OPC) in concrete production, thereby offering a reduced carbon footprint and costs [ 13 , 14 ]. However, its sulfuric acid extraction origins with elevated SO 3 levels necessitate caution in its use to maintain cement stability [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded with the highly precise prediction of UHPC compressive strength, having an R 2 of 0.96. Lu et al (2019) have applied the Support Vector Machine (SVM) modelling approach to determine the lithium-slag effect on the properties of cementitious mortar and resulted in an 11% enhanced and improved prediction performance of SVM with respect to other ML models. Similarly, Solhmirzaei et al (2020) also reported the effective prediction of SVM modelling in the case of shear capacity for UHPC beams.…”
Section: Introductionmentioning
confidence: 99%